Alteration of serum lipid profile and its prognostic value in head and neck squamous cell carcinoma. (20th July 2015) - Li, Gang; Da, Mingjie; Zhang, Wei; Wu, Heming; Ye, Jinhai; Chen, Jie; Ma, Lu; Gu, Ning; Wu, Yunong; Song, Xiaomeng
Abstract : Background: Several serum lipid components have been implicated in the development of cancer. However, the prognostic significance of serum lipid components in head and neck squamous cell carcinoma is unknown. Here, we investigated the predictive value of serum lipid profile at diagnosis and in the overall survival of the patients. Methods: The study population consists of 136 pathologically confirmed head and neck squamous cell carcinoma cases diagnosed between years 2009 and 2014 at a tertiary medical center. Levels of preoperative serum lipid component's total cholesterol, triglycerides, high‐density lipoprotein, low‐density lipoprotein, apolipoprotein A, apolipoprotein B, and lipoprotein (a) were compared between patients and normal controls matched for age and gender. Serum lipid profiles and their association with clinical parameters were analyzed. The effects of the serum lipid components on survival were examined using the proportional hazards regression model to estimate hazard ratio. Results: Significant lower levels of cholesterol, low‐density lipoprotein, apolipoprotein A, and apolipoprotein B were found in patients with oral cancer ( P < 0.0001). However, a significantly higher level of lipoprotein (a) was found in the cancer group ( P < 0.0001). Patients with higher lipoprotein (a) had significantly shorter overall survival than those with lower lipoprotein (a) ( P = 0.0042). Multivariate analysis showed that both higher lipoprotein (a) and lymph node metastasis are independent prognostic factors in the patient population ( P < 0.01). Conclusion: A higher lipoprotein (a) was associated with poorer prognosis and might be a novel marker in patients with head and neck squamous cell carcinoma.